ANALYSIS OF EMISSION CHARACTERISTICS OF A B35 WITH HYDROGEN PEROXIDE EMULSION WITHOUT SURFACTANTS - Agus Mulyana; Muhammad Fariedz Irawan; Fakhrul Afif Uzair; Dhani Avianto Sugeng; Kurnia Fajar Adhi Sukra; Frendy Rian Saputro; Wira Jazair Yahya; Rizqon Fajar; Boni Sena; Ujiburrahman (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2026)
The use of hydrogen peroxide or H2O2 as a fuel additive is known to improve the combustion quality of conventional fuels, including Indonesia’s biodiesel B35. Because H2O2 and B35 do not mix naturally, the H2O2 must be emulsified into B35 to ensure stable fuel delivery and consistent combustion. Conventional emulsification methods typically rely on chemical surfactants, which require a separate preparation step. This study therefore aimed to evaluate the effects of an H2O2–B35 emulsion (HPBE) produced without surfactants on diesel engine performance and emissions. The emulsion was prepared using B35 as the base fuel and 10% (v/v) of 30% aqueous H2O2 as the dispersed phase. Emulsification was carried out using an inline mixer known as the Real-Time Non-Surfactant Emulsion Fuel Supply System (RTES). Engine tests were performed on a Kubota Z482 operating at a constant speed of 2800 rpm under loads of 2.7, 8, 13, 19, and 26 Nm, applied using a Cussons eddy current dynamometer. The parameters measured include Brake Specific Fuel Consumption (BSFC), exhaust gas temperature (EGT) as well as Carbon Monoxide (CO), Carbon Dioxide (CO2), Nitrogen Oxide (NOx) emissions, and smoke opacity. The results showed that, compared to B35, HPBE improved all measured parameters across all loads. BSFC decreased, with the maximum reduction of 22.9% occurring at 8 Nm. At full load, HPBE produced the maximum reductions in smoke opacity (31.3%), CO (29.5%), and CO2 (11.2%). Meanwhile, the maximum NOx reduction of 14.3% was observed at 75% load.